Trigonometric interval-valued neutrosophic set setting with reciprocal fractional function using a finite weighted method - Murugan Palanikumar; Nasreen kausar; Tonguc Cagin (Neutrosophic Sets and Systems)
This paper presents a new method for creating a trigonometric interval-valued neutrosophic set via reciprocal fractional function. This article will cover the concepts of geometric, generalized weighted averaging, trigonometric interval-valued neutrosophic reciprocal fractional weighted averaging, and generalized weighted geometric. We used an aggregating model to get the weighted average and geometric. To further examine a number of sets with important qualities, the algebraic techniques listed below will be applied.